FinTech E-Commerce Payment Application User Experience Analysis during COVID-19 Pandemic - Abdillah, Leon A. (Universitas Negeri Semarang, 2020)
Application of information technology in the era of big data and cloud computing has led to the trend of electronic payments through financial technology, or FinTech. One of the most popular FinTech applications in Indonesia is Go-Pay in the Gojek start-up application. This research will analyze how the FinTech Go-Pay user experience both for transactions on Gojek and at merchants that collaborate with Gojek. User Experience (UX) is analyzed using the User Experience Questionnaire which consists of 6 (six) variables (Attractiveness, Perspicuity, Efficiency, Dependability, Stimulation, and Novelty). Total data collected amounted to 258. After analyzing the calculation results, the mean scores are obtained in the following order: Efficiency, Perspicuity, Stimulation, Attractiveness, Dependability, and Novelty. Then when compared with benchmark data the following sequence is obtained: Efficiency, Perspicuity, Stimulation, Attractiveness, Dependability, and Novelty. Overall the Go-Pay service is efficient and perspicuity, but the Go-Pay service needs to improve its novelty.